Literature Review : Asuhan Keperawatan Gerontik pada Pasien Lansia yang Mengalami Hipertensi dengan Menggunakan Proses Keperawatan - Lucky Amanda; Syifa Putri Ramadhanti; Elva Nur Setyani; Gita Fitriani; Gusti Nadhif Khalil Farras; Sri Ariyanti (Jurnal Kajian dan Penelitian Umum, 2025)
Background : : The elderly are elderly patients who are susceptible to disease due to a decrease in the physiological function of the body due to the aging process. So that various kinds of health problems that often occur in the elderly such as hypertension. Hypertension is a condition where systole and dystole pressure exceeds normal limits (systole pressure above 140 mmHg and diastole above 90 mmHg). Such high blood pressure can cause vascular complications to increase morbidity and mortality.The purpose of this literature riview : To analyze the gerontic nursing process for the elderly who experience hypertension.Research methods : Journal data sourcing through case study design.Results : Analysis of journal reviews found differences in the level of effectiveness between elderly gymnastics (70%) and reflexology (30%) where elderly gymnastics is more influential than reflexology in reducing blood pressure.Conclusion : There is a gerontic nursing process for the elderly who experience hypertension.